ANALISIS INTERAKSI SIMBOLIK YANG MEMBENTUK POLA KOMUNIKASI DINAMIS PADA KOMUNITAS PESISIR KABUPATEN JEMBER - Fajar, Aryo (Jurnal Sosial Ekonomi Pertanian, 2011)
In the economy aspect, ocean resources are main potential that was activated the rural economy in coastal area, which is in general, the rural economy activity in coastal area was fluctuated. Location of the research was chosen by purposive method, that located in Puger Sub district Jember District. Type of the research will use descriptive qualitative. Interaction that was happened in fisherman correlation caused by social contact in coastal area activity, which is about profession as fisherman although in social society activity. The presence of consideration, attitude, and measure of condition in south coastal fisherman community in Jember District, have tight correlation with culture value system in community. The presence of symbol status will strengthen the position of the person in community of coastal society, so it can be sign of self existence (identity). Reciprocity norm in managing social correlation have been showed to each side.Keywords : Coastal area, Social exchange, interaction, social networks